PERBEDAAN PEROLEHAN NILAI MATA KULIAH ANTE NATAL CARE (ANC) - Nani Murtriyani (Akademi Kebidanan La Tansa Mashiro, 2013)
The purpose of this study was to determine the correlation of high school education background to the value of subjects Askeb I Ante Natal Care (ANC) on the student at the Academy of Midwifery Rangkasbitung LTM 2009. The research was conducted on the entire student generation II and generation III is in LTM Rangkasbitung Midwifery Academy in 2007-2009, as many as 97 students and a cross-sectional study design, data collection using secondary data. Analyses of the data used are univariate (frequency distributions) and bivariate analyzes to test Kai Squares. The research concludes that there is a difference in course grades askeb I (ANC) from the Social Sciences and the Academy of Natural Sciences in Midwifery LTM Rangkasbitung. This means that students with an educational background IPA Askeb I would have rated better than students whose educational background IPS.